Kontribusi adversity quotient terhadap student engagement pada pembelajaran blended learning di SMAN x Singosari - Addini Fahira; Uun Zulfiana (Cognicia, 2022)
The sector that has felt the impact of the Covid-19 pandemic is the education sector. Education that is carried out using blended learning is chosen by schools so that they can continue the learning process. Increasing student engagement during blended learning is by instilling an adversity quotient in each individual. So that with the adversity quotient in the individual, students will easily change all problems and obstacles in blended learning into a challenge that can be faced by all students. The purpose of this study was to determine the contribution of adversity quotient to student engagement in blended learning at SMAN X Singosari. This study uses a quantitative approach with a causal design. The subjects of this study amounted to 283 students at SMAN X Singosari using cluster sampling technique. Data analysis in this study used simple linear regression analysis using JASP to see the contribution of X to Y. The results showed that there was a significant positive contribution between the adversity quotient variable on student engagement in blended learning at SMAN X Singosari (r = 0.439; p < 0.05). Adversity quotient during blended learning has a positive effect of 19.3% on student engagement.   Keywords: Adversity quotient, blended learning, high school students, student engagement